Efektivitas Repellent dari Ekstrak Akar Tuba (Derris elliptica) terhadap Daya Hinggap Nyamuk Aedes aegypti - Galih Zatmiko Alan; Erni Yohani Mahtuti (Lembaga Pengembangan Kinerja Dosen, 2025)
Dengue fever is a disease caused by the dengue virus and is transmitted through the Aedes aegypti mosquito vector. One of the prevention of dengue disease that can be done is the use of repellent. Herbal insecticides are insecticides whose basic ingredients are derived from plants. One of the plants that can be used is tubal root plants. The purpose of this study is to determine the effectiveness of repellent from tuba root extract on the perchability of Aedes aegypti mosquitoes. This study is an experimental research using the Complete Random Design (RAL) method which consists of 4 treatment levels: 5 ml tuba root extract, 10 ml tuba root extract, 15 ml tuba root extract and 20 ml tuba root extract. The results of this study obtained the total perching power of Aedes aegypti mosquitoes against repellent of tubal root extract which was carried out in 6 repetitions, namely in the composition of A1 (5 ml) as much as 4%, the composition of A2 (10 ml) as much as 1.6%, the composition of A3 (15 ml) as much as 0.83%, the composition of A4 (20 ml) as much as 0.3%. The results of the one-way anova test obtained a significant result of 0.005 (p<0.05) showing the repellent effect of tuba root extract on Aedes aegypti mosquitoes. This study proves that the repellent of tuba root extract that is the most effective against the perching power of Aedes aegypti mosquitoes, namely repellent of tuba root extract with a composition of A4 (20 ml).